(untitled) (Research, Society and Development, 2020)
Analyzes the possibility of carrying out educational practices of geography integrated with technical training of medium level in environment in a state school of professional education (EEEP) of ceará in the light of Historical-Critical Pedagogy (PHC), in the perspective of the teaching and student social practice in formal and non-formal educational spaces. As a central question, we have: how to work with pedagogical praxis that promotes the collectivity of students in correlation with teachers in the teaching and learning process that wants to transform the social reality of high school subjects integrated in an EEEP? The analysis started from direct observation in the pedagogical interactions between the Geography teacher, the technical teacher of Water Resources and the 45 students of the 3rd grade of that school. The methodology brings marx’s Dialectical Materialism as a reference framework, in addition to an exploratory reflective study, seeking to highlight the moments of initial social practice, problematization, instrumentalization, catharsis and final social practice present in the PHC method, proclaimed by the teacher and philosopher Dermeval Saviani. The results showed the collective construction of the class and its integrative dynamics in its course, bringing teachers and students closer together in the teaching and learning process in an organic and meaningful way. The considerations lead to a class strategy that allows greater interrelationship between teachers and students, as well as the integration of the disciplines of general and technical professional training in a collaborative way.